THE CONSERVATION NUMBERS IN THE PETRI NET MODEL OF THREE-PHASE TRAFFIC LIGHTS WITH THE NORWEGIAN SYSTEM - Tomi Tristono; Setiyo Daru Cahyono; Joko Triono; Mochamad Sidqon; Seno Aji; Sudarno Sudarno; Nanang Junaedi (Universitas Jenderal Soedirman, 2025)
The Petri net model can be used to represent the discrete state behavior structure of traffic light signals. The Petri net model is also capable of presenting three-phase traffic light scheduling synchronization. This study aims to examine the three-phase traffic light Petri net model that implements the Norwegian system. The Petri net model must pass validation and verification tests, including the use of several Place-Invariants, its boundedness property, conservation, coverability for all states, and simulation. The study results indicate that the model complies with all Place-Invariants, meets all required properties, and the simulation is also accurate. Place-Invariants in each phase must include a dummy. The three-phase traffic light Petri net model with the Norwegian system has a conservation number that applies to the model as a whole. The conservation number is an extension of Place-Invariant that only applies partially to the model.